PENGARUH MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN (Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Ahmad Farhan Makky; Muhammad Agus Salim; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study is intended to explain the effect of working capital on profitabilityin food and beverage companies in Indonesia Stock Exchange (BEI) in 2012-2016. The population of this research is all food and beverage companies in BEIin 2012-2016. The sample was taken by using purposive sampling method so that11 eligible companies as sample. This study uses secondary data and multipleregression analysis method.The results showed. Significant influence on profitability, significantliquidity variables. Simultaneously variable working capital and liquidity aresignificant.Keywords: Profitability, Working Capital, Liquidity